2017
DOI: 10.3390/en10020224
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Native Microalgae from the Peruvian Amazon with Potential for Biodiesel Production

Abstract: Biodiesel production from microalgae triacylglycerols is growing, because this feedstock is a more sustainable and advantageous alternative. In this study, we isolated and identified fourteen strains of native microalgae from the Peruvian Amazon. These strains showed great heterogeneity in biomass productivity, lipid productivity and lipid content, and thus, three of them (Acutodesmus obliquus, Ankistrodesmus sp. and Chlorella lewinii) were selected for further evaluation under culture of nitrogen-sufficient (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 81 publications
(125 reference statements)
2
16
0
Order By: Relevance
“…In general, microalgae have variations in the content of their biochemical parameters. For example, Chlorella lewinii showed a higher protein content (31.2%), Ankistrodesmus sp., a higher total lipid content (39.5%), and Acutodesmus obliquus a higher percentage of carbohydrates (49.6%) compared to other freshwater microalgae [21]. These parameters vary even more in conditions of physiological stress to which microalgae are subjected, as evidenced in the species of microalgae that accumulated a greater amount of total lipids (mg/g dry biomass) when grown in media without nitrogen; Ankistrodesmus nannoselene (316 mg/g dry biomass), Ankistrodesmus sp.…”
Section: Humidity and Ashesmentioning
confidence: 90%
See 1 more Smart Citation
“…In general, microalgae have variations in the content of their biochemical parameters. For example, Chlorella lewinii showed a higher protein content (31.2%), Ankistrodesmus sp., a higher total lipid content (39.5%), and Acutodesmus obliquus a higher percentage of carbohydrates (49.6%) compared to other freshwater microalgae [21]. These parameters vary even more in conditions of physiological stress to which microalgae are subjected, as evidenced in the species of microalgae that accumulated a greater amount of total lipids (mg/g dry biomass) when grown in media without nitrogen; Ankistrodesmus nannoselene (316 mg/g dry biomass), Ankistrodesmus sp.…”
Section: Humidity and Ashesmentioning
confidence: 90%
“…Once the purified microalgal DNA has been obtained, the following quality control methods are recommended. Electrophoretic analysis allows nucleic acid molecules to be separated by size that is dependent on the density of the matrix used (19)(20)(21). High molecular weight DNA should produce a single, bright band with little to no smearing.…”
Section: Methodsologymentioning
confidence: 99%
“…It has been reported that the lipid yield in cultured algae may increase as nitrogen in the culture media gets depleted (Tan et al 2016). Nitrogen starvation causes the rechanneling of photosynthetic ATP towards lipid biosynthesis (Cobos et al 2017). Induced nitrogen starvation may therefore lead to optimum lipid yield.…”
Section: Discussionmentioning
confidence: 99%
“…This provides a large genomic pool from which potential strains for biodiesel production can be isolated. The applicability of microalgae in biodiesel production has been widely studied (Duong 2016;Tan et al 2016;Cobos et al 2017;Kalsum et al 2018;Li et al 2020;Khalaji et al 2021). Nevertheless, selection of a suitable microalgal strain is one of the main challenges affecting commercial microalgal biodiesel production (Mallick et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To isolate microalgae, serial dilutions of enriched flask were performed, and 50 μL samples from 1, 2, 4, and 6 dilution fractions were inoculated to a new 500 mL flask containing 250 mL of Bold Basal Medium (BBM) (Arif et al, 2020). A volume of 50 μL from different dilutions was transferred to wells of microtiter plates that had 200 μL BBM and were kept at 22°C under continuous illumination for 3 weeks of 850 Lux with a 16/8 h light/dark cycle using T8 led tube light (G13/9W 6000 K, Brilliant, Germany) (Cobos et al, 2017). The culture's purity was confirmed by repeated culturing and microscopic examinations.…”
Section: Isolation and Identification Of Microalgaementioning
confidence: 99%